Podoplanin Gene Disruption in Mice Promotes in vivo Neural Progenitor Cells Proliferation, Selectively Impairs Dentate Gyrus Synaptic Depression and Induces Anxiety-Like Behaviors - Cicvaric, Ana; Sachernegg, Hannah M.; Stojanovic, Tamara; Symmank, Dörte; Smani, Tarik; Moeslinger, Thomas; Uhrin, Pavel; Monje, Francisco J. (Frontiers in Cellular Neuroscience, 2020)
Podoplanin (Pdpn), a brain-tumor-related glycoprotein identified in humans and animals, is endogenously expressed in several organs critical for life support such as kidney, lung, hearth and brain. In the brain, Pdpn has been identified in proliferative nestin-positive adult neural progenitor cells and in neurons of the neurogenic hippocampal dentate gyrus, a structure associated to anxiety, critical for learning and memory functions and severely damaged in people with Alzheimer´s disease. The in vivo role of Pdpn in adult neurogenesis and anxiety-like behavior remained however unexplored. Using mice with disrupted Pdpn gene as a model organism and applying combined behavioral, molecular biological and electrophysiological assays, we here show that the absence of Pdpn selectively impairs long-term synaptic depression in the neurogenic dentate gyrus without affecting the CA3-Schaffer´s collateral-CA1 synapses. Pdpn deletion also enhanced the proliferative capacity of dentate gyrus neural progenitor cells and diminished survival of differentiated neuronal cells in vitro. In addition, mice with podoplanin gene disruption showed increased anxiety-like behaviors in experimentally validated behavioral tests as compared to wild type littermate controls. Together, these findings broaden our knowledge on the molecular mechanisms influencing hippocampal synaptic plasticity and neurogenesis in vivo and reveal Pdpn as a novel molecular target for future studies addressing general anxiety disorder and synaptic depression-related memory dysfunctions.